2013
DOI: 10.1111/imre.12041
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Concentration and Nonprofit Organizations: The Political and Urban Geography of Immigrant Services in Boston, Massachusetts

Abstract: This article considers the geographic distribution of nonprofit organizations serving immigrants across municipalities within the Greater Boston area in an effort to identify variations in the levels of assistance available to major foreign-born populations in the region. The analysis relies on data from the Census and the National Center for Charitable Statistics. Results suggest that geographic context matters, including immigrant settlement patterns, racial heterogeneity, and fiscal and institutional charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Yet, research shows that these resources are unevenly distributed (Joassart-Marcelli, 2013;Joassart-Marcelli & Martin, 2014;Joassart-Marcelli & Wolch, 2003). Figure 5 confirms these findings and illustrates gaps in access to nonprofit organizations claiming employment assistance or services to Latinos as their main purpose.…”
Section: Urban Geography 833mentioning
confidence: 76%
“…Yet, research shows that these resources are unevenly distributed (Joassart-Marcelli, 2013;Joassart-Marcelli & Martin, 2014;Joassart-Marcelli & Wolch, 2003). Figure 5 confirms these findings and illustrates gaps in access to nonprofit organizations claiming employment assistance or services to Latinos as their main purpose.…”
Section: Urban Geography 833mentioning
confidence: 76%
“…Findings align with other research challenging the assumption that place-based co-ethnic density—as found in “ethnic enclaves”—is universally beneficial to health (Ebert and Ovink, 2014; Portes and Rumbaut, 2014). Though co-ethnic density may be protective in some domains, particularly with respect to resources generated within immigrant communities (Bécares, 2014; Bertrand et al, 2000; Joassart-Marcelli, 2013; Menjívar, 1997; Portes and Rumbaut, 2014), density may also trigger discrimination and policy responses that are harmful to migrant health (Chand and Schreckhise, 2015; Ebert and Ovink, 2014; Ybarra et al, 2016).…”
Section: Implications For Research and Public Health Practicementioning
confidence: 99%
“…States that pass omnibus laws contain wide diversity in public support for these laws at the local level (Koralek et al, 2009; Pham, 2008). They also vary in the presence of resources for migrant populations (Bécares et al, 2012; Joassart-Marcelli, 2013; Menjívar, 1997). In some states, Medicaid/CHIP programs are highly decentralized and administered at the county level (Perreira et al, 2012); policies and procedures in county offices could exacerbate (or limit) the laws’ impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a nonprofit does not have social media innovators in its network, then late adoption may never occur. For immigrant-serving nonprofit organizations in historic centers of immigration such as New York city, NY, or Los Angeles, CA, this may not be a problem but increasingly immigrants are residing in new gateway states and outside cities (Joassart-Marcelli, 2013). These places, for example, in rural Georgia or Tennessee, may be prone to the isolation that will work against nonprofits learning from others in their community.…”
Section: Factors That Relate To Nonprofit Adoption Of Social Mediamentioning
confidence: 99%